2015
DOI: 10.3746/jkfn.2015.44.3.455
|View full text |Cite
|
Sign up to set email alerts
|

Quality Characteristics of Low-Dose Electron Beam Irradiated-Imported Navel Orange during Storage at Room Temperature (20℃)

Abstract: This study investigated the effects of low-dose electron beam irradiation treatment on the physicochemical and sensorial properties of imported navel oranges during storage at 20°C for 12 days. The samples were irradiated at doses of 0.2, 0.4, 0.6, 0.8, and 1.0 kGy, after which changes in color value, hardness, Brix/acid ratio, total sugar contents, reducing sugar contents, vitamin C contents, and sensory evaluation were investigated. There were no significant differences between non-irradiated and irradiated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…Total vitamin C content (AA+DHA) of California and Florida varieties is 83 and 63 mg kg -1 , respectively (Vanderslice et al, 1990). Some reports on evaluating the effect of irradiation on vitamin C content of oranges showed that orange, mandarin and acid lime samples were irradiated at 1.5 kGy using gamma rays and the vitamin C contents of these fruit declined by 16 %, 27 % and 29 %, respectively (Ladaniya et al, 2003), in blood oranges, irradiation with 0.25 and 0.5 kGy slowed the loss of ascorbic acid (AA) during six weeks storage, resulting in higher AA levels in oranges irradiated with 0.5 kGy (Khalil et al, 2009), irradiation (0.2 -0.6 kGy) on 'Lane Late' Navel oranges had no effect on vitamin C retention (McDonald et al, 2013), irradiated (0 -0.2 kGy) and non-irradiated Valencia oranges had similar vitamin C content (De Bortoli et al, 2015) and vitamin C was insignificantly different between irradiated (0.2 -1 kGy) and non-irradiated Navel orange fruit (Cho et al, 2015). Our results revealed that gamma irradiation had a significant effect (P <0.05) on the vitamin C level of fruit juice of 'Jaffa' orange in all intervals except 15 d intervals of cold storage (Table 3).…”
Section: Pectin Vitamin C Total Carotenoids (Tc) and Colormentioning
confidence: 99%
“…Total vitamin C content (AA+DHA) of California and Florida varieties is 83 and 63 mg kg -1 , respectively (Vanderslice et al, 1990). Some reports on evaluating the effect of irradiation on vitamin C content of oranges showed that orange, mandarin and acid lime samples were irradiated at 1.5 kGy using gamma rays and the vitamin C contents of these fruit declined by 16 %, 27 % and 29 %, respectively (Ladaniya et al, 2003), in blood oranges, irradiation with 0.25 and 0.5 kGy slowed the loss of ascorbic acid (AA) during six weeks storage, resulting in higher AA levels in oranges irradiated with 0.5 kGy (Khalil et al, 2009), irradiation (0.2 -0.6 kGy) on 'Lane Late' Navel oranges had no effect on vitamin C retention (McDonald et al, 2013), irradiated (0 -0.2 kGy) and non-irradiated Valencia oranges had similar vitamin C content (De Bortoli et al, 2015) and vitamin C was insignificantly different between irradiated (0.2 -1 kGy) and non-irradiated Navel orange fruit (Cho et al, 2015). Our results revealed that gamma irradiation had a significant effect (P <0.05) on the vitamin C level of fruit juice of 'Jaffa' orange in all intervals except 15 d intervals of cold storage (Table 3).…”
Section: Pectin Vitamin C Total Carotenoids (Tc) and Colormentioning
confidence: 99%